Characteristic of Steady-State Flow Force on the Cone Valve Based on Orthogonal Test Method - Liu, Xiumei; He, Jie; Ma, Jichao; Li, Beibei; Xiang, Shaobin; Zhang, Yujia; Liu, Qihang; Xie, Fangwei (Frontiers in Energy Research, 2022)
The steady-state flow force is the fundamental reason that affects the pressure stability, which will reduce the control performance of a hydraulic valve. A mathematical model of the axial steady-state flow force on the valve core is proposed to master the principle and characteristics of steady-state flow force. For understanding the dynamic changes of the steady-state flow force, a two-dimensional axisymmetric model is built to discuss the value of flow force. Different geometric parameters and operating conditions have different effects on the performance of the valve, and analyzing a variety of parameters is difficult because of the complexity of the test. Therefore, the geometric parameters and operating conditions in the steady-state flow force were optimized by the orthogonal test-optimization method. The main significant factors affecting the performance of steady-state flow force on the cone valve core are determined by extreme difference analysis, which are the opening and pressure differential, respectively. Furthermore, a test ring is built to measure the steady-state flow force. The results show that the greater the pressure differential is, the greater the steady-state flow force is. The steady-state flow force does not increase linearly, but increases first and then decreases with the increase of the opening. The study will lay the foundation to precise axial flow force prediction and reference for design optimization of the valve.